1998
DOI: 10.1002/jhet.5570350418
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis and photolysis of 1‐aroylamino‐4,5‐diaryl‐1,2,3‐triazoles: Generation and thermal transformations of 4,5‐diaryl‐1,2,3‐triazolyl radicals

Abstract: The pyrolysis of 1‐aroylamino‐4,5‐diphenyl‐1,2,3‐triazoles 1 yields, pressumably via the 4,5‐diphenyl‐1,2,3‐triazolyl radical (2a), 2,3‐diphenyl‐2H‐azirine (11a) and 2‐aryl‐4,5‐diphenylimidazoles 14 as the major products. Upon irradiation 1‐benzoylamino‐4,5‐diphenyl‐1,2,3‐triazole (1a) gives 4,5‐diphenyl‐1 (2)H‐1,2,3‐triazole (4a) via the 1,2,3‐triazolyl radical 2a, together with benzamide (5a) and 1,2‐bisbenzoylhydrazine (6a). Products 5a and 6a result from the benzoylamino radical 3a by hydrogen atom abstrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A concrete understanding of specific bond cleavage reactions during the ZIF-8 decomposition process under the conditions imposed during this study enables formation of a possible chemical structure after decomposition and refinement of thermal decomposition reaction eqs and . TGA decomposition studies have confirmed onset decomposition temperatures of approximately 200–300 °C for unsubstituted and substituted imidazole and triazole molecules. , Detailed analyses of single methyl substituted imidazole decomposition reaction mechanisms were not found. However, previous work on the thermal decomposition of imidazole suggests the formation of vinylcarbene through a reaction pathway involving competitive reactions of imidazole cyclization to 3H-imidazole and nitrogen extrusion/elimination to form vinylcarbene, which then rearranges into more stable propyne .…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A concrete understanding of specific bond cleavage reactions during the ZIF-8 decomposition process under the conditions imposed during this study enables formation of a possible chemical structure after decomposition and refinement of thermal decomposition reaction eqs and . TGA decomposition studies have confirmed onset decomposition temperatures of approximately 200–300 °C for unsubstituted and substituted imidazole and triazole molecules. , Detailed analyses of single methyl substituted imidazole decomposition reaction mechanisms were not found. However, previous work on the thermal decomposition of imidazole suggests the formation of vinylcarbene through a reaction pathway involving competitive reactions of imidazole cyclization to 3H-imidazole and nitrogen extrusion/elimination to form vinylcarbene, which then rearranges into more stable propyne .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Quaternary amines such as tetrapropylammonium hydroxide or tetrapropylammonium bromide decompose into lower amines and olefin products in the presence of their strong basic substituents (OH – and Br – ) at temperatures greater than 400 °C through a Hofmann/E2 elimination mechanism. During ZIF-8 carbonization an olefin gaseous product and a solid residual lower amine containing structure are formed without significant presence of a strong base and occurs at lower temperatures as compared to quaternary amine decomposition, which possibly precludes a Hofmann/E2 elimination mechanism as the major decomposition reaction. The works by Aniyappan and Maroulis involving the pyrolysis of imidazole and triazole ligands suggest thermolytic bond cleavage as a main mechanism for imidazole thermal decomposition. , Both authors concluded that azirine molecules were formed after thermal decomposition.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1998, Hadjiantou‐Maroulis et al [4] found the pyrolysis of 1‐aroylamino‐4,5‐diphenyl‐1,2,3‐triazoles ( I ) yields 2,3‐diphenyl‐2H‐azirine ( II ) and 2‐aryl‐4,5‐diphenylimidazoles ( III ) as the major products (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Hadjiantou‐Maroulis et al [4], we found a novel synthesis of imidazoles XI from 2‐aminoacrylates IX and azides X . To our knowledge, no report has described such a one‐pot procedure to synthesize imidazoles XI from 2‐amidoacrylates IX (Scheme ).…”
Section: Introductionmentioning
confidence: 99%